New “Omics” Approaches as Tools to Explore Mechanistic Nanotoxicology - Ventura, Célia (2022)
In the last years, “omics” approaches have been applied to study the toxicity of nanomaterials (NM) with the aim of obtaining insightful information on their biological effects. One of the most developed “omics” field, transcriptomics, expects to find unique profiles of differentially expressed genes after exposure to NM that, besides providing evidence of their mechanistic mode of action, may also be used as biomarkers for biomonitoring purposes. Moreover, several NM have been associated with epigenetic alterations, i.e., changes in the regulation of gene expression caused by differential DNA methylation, histone tail modification and microRNA expression. Epigenomics research focusing on DNA methylation is increasingly common and the role of microRNAs is being better understood, either promoting or suppressing biological pathways. Moreover, the proteome is a highly dynamic system that changes constantly in response to a stimulus. Therefore, proteomics can identify changes in protein abundance and/ or variability that lead to a better understanding of the underlying mechanisms of action of NM while discovering biomarkers. As to genomics, it is still not well developed in nanotoxicology. Nevertheless, the individual susceptibility to NM mediated by constitutive or acquired genomic variants represents an important component in understanding the variations in the biological response to NM exposure and, consequently, a key factor to evaluate possible adverse effects in exposed individuals. By elucidating the molecular changes that are involved NM toxicity, the new “omics” studies are expected to contribute to exclude or reduce the handling of hazardous NM in the workplace and support the implementation of regulation to protect human health.